2019
DOI: 10.1002/rrq.280
|View full text |Cite
|
Sign up to set email alerts
|

Sound Stories: Using Nonverbal Sound Effects to Support English Word Learning in First‐Grade Music Classrooms

Abstract: Early vocabulary knowledge is vital for later reading comprehension and academic success. Studies have found that augmenting explicit teaching of word meanings with nonverbal visual aids, particularly pictures and gestures, assists young learners in building rich lexical representations. Research has focused on the effects of visual supports in fostering word knowledge but has not considered the effectiveness of using sound‐based supports. Working from a semiotics perspective, the authors used a music instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Given children’s increased ability to interpret the intended meanings of representations by the primary grades (Nelson, 2007), nonverbal supports may be particularly effective for abstract words. Only a few of the reviewed studies measured abstract word learning (August, Artzi, Barr, & Francis, 2018; de Nooijer et al, 2013; Hadley et al, 2016; Lawson‐Adams & Dickinson, 2019a, 2019b). Several of the studies reported an increase in definitional and depth of word knowledge for abstract nouns when nonverbal supports were used, even for non‐native English speakers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given children’s increased ability to interpret the intended meanings of representations by the primary grades (Nelson, 2007), nonverbal supports may be particularly effective for abstract words. Only a few of the reviewed studies measured abstract word learning (August, Artzi, Barr, & Francis, 2018; de Nooijer et al, 2013; Hadley et al, 2016; Lawson‐Adams & Dickinson, 2019a, 2019b). Several of the studies reported an increase in definitional and depth of word knowledge for abstract nouns when nonverbal supports were used, even for non‐native English speakers.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, primary‐grade students experience difficulty in learning abstract words (Hadley et al, 2016) and may need additional support beyond verbal instruction regardless of their language background. There is evidence that pushing students to reflect on the semantic features of nonverbal supports may deepen word knowledge of abstract words, particularly abstract nouns (Lawson‐Adams & Dickinson, 2019a, 2019b). However, as previously discussed, more research is needed to better understand whether different modalities of nonverbal supports (e.g., gestures, pictures, sounds) can effectively support students in learning abstract words.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of music integration in the preschool setting is clear when making comparisons of the language learning of preschoolers in classrooms where the teachers received formal music education training versus those in classrooms of teachers who had not (Lorenzo et al., 2014). A recent study found that first-grade children learned more vocabulary and had a richer depth of knowledge when word learning was paired with sound-effects (Lawson-Adams and Dickinson, 2019); the researchers hypothesized that the sound effects created using instruments not only increased attention but likewise supplied additional semantic information that facilitated learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Music class is a good way to cultivate students' aesthetic taste and cultural qualities [1]. In music teaching, educators should enrich and rationalize the teaching methods and tools, pay attention to students' overall feeling of the music class and music teaching, and enable them to fully experience the charm of music as an art form [2,3] visualization of music teaching is a psychological phenomenon of music produced based on synesthesia, and it contains a variety of music teaching methods [4]. In actual teaching process, music teachers actively attempt to give back the class to students, and apply more interesting music teaching methods to the students [5,6].…”
Section: Introductionmentioning
confidence: 99%